2016
DOI: 10.1182/blood-2015-10-675173
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan from the gut microbiota governs the lifespan of circulating phagocytes at homeostasis

Abstract: Key Points The intestinal microbiota regulates the steady-state survival and turnover kinetics of circulating neutrophils and inflammatory monocytes. The cytoplasmic peptido-glycan sensor Nod1 relays microbial signals into IL-17A–dependent stimulation of myeloid cell persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 72 publications
(86 reference statements)
5
74
0
Order By: Relevance
“…While tumor‐derived factors and the tumor microenvironment can reprogram marrow to drive granulopoiesis and generation of neutrophils with distinct phenotypes, other factors may also do so. For example, recent studies point to the microbiome influencing neutrophil lifespan and function, including the propensity to generate NETs . The influence of the microbiome on neutrophil biology may be of particular relevance in patients with cancer where microbiome alterations can result from several factors, including mucosal injury from chemotherapy and radiation and the widespread use of antibiotics.…”
Section: Future Therapeutic Strategies Targeting Neutrophils In the Tmentioning
confidence: 99%
“…While tumor‐derived factors and the tumor microenvironment can reprogram marrow to drive granulopoiesis and generation of neutrophils with distinct phenotypes, other factors may also do so. For example, recent studies point to the microbiome influencing neutrophil lifespan and function, including the propensity to generate NETs . The influence of the microbiome on neutrophil biology may be of particular relevance in patients with cancer where microbiome alterations can result from several factors, including mucosal injury from chemotherapy and radiation and the widespread use of antibiotics.…”
Section: Future Therapeutic Strategies Targeting Neutrophils In the Tmentioning
confidence: 99%
“…The resulting agglomeration of immune cells and structures helps to manage and contain the microbiota at the mucosa 23, 24. The microbiota also drives the maturation of systemic immunity beyond the confines of the mucosa, including in major immune tissues such as the bone marrow and spleen 25, 26, 27, 28, 29, 30. The importance of host–microbiota interactions for our health has been highlighted by clinical studies and work with animal models demonstrating that microbiota dysbiosis is associated with diseases and immune dysfunctions in both intestinal and extra‐intestinal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in mice has demonstrated that PGN derived from gut microbiota can influence remote tissues and organs [31,32] . In flies, gut Ecc release PGN that can cross the gut epithelium and its surrounding muscles and reach the hemolymph where it activates the NF-κB pathway in FB cells [33] .…”
Section: Drosophila Slc15 Transporters Are Not Required For Pgn Transmentioning
confidence: 99%